Estimate the Endemic (SIR) Model of Monkey Pox Disease - Suhad Ali Shaheed Al-Temimi, Hamid Saad Nour AL-Shammrty (Mathematical Statistician and Engineering Applications, 2022)
Diseases are of great concern to the human race and we are still affected by the dramatic descriptions that reach us from the past, including the "Black Death", the plague that spread throughout Europe from 1347 to 1352 and caused 25 million victims, far from our lives, but Recent events, including the spread of the Corona pandemic, remind us that disease is a real problem for us.The definition of (endemic, epidemic, and pandemic) can be defined as endemic diseases that are always present throughout an area or group of people and remain more or less constant. Such as measles, smallpox, polio, etc.An epidemic can be defined as a disease that increases unexpectedly among a large number of people or an area. An example is Ebola, which spread rapidly throughout West Africa.A pandemic is a disease that is transmitted across multiple countries or continents, affecting large numbers of people. An example of this is COVID-19.Mathematical models represent a descriptionof infection increasing in a population over time. Epidemiological models divide the population intothree groups, each group contains individuals who are identical in terms of their condition with regard to the disease. The SIR model is a basic model from which many models are derived, and according to the nature of the epidemic, the three main parts are (Susceptible (S), Infected (I), Recovered or Resistant (R)). Diseases in which individuals acquire permanent immunity. And the endemic to which this model can be applied, include measles, smallpox, mumps, typhoid fever, and diphtheria.The research deals with Monkeypox (MPXV) a rare viral die characterized by fever and a rash. This disease is a zoonotic viral disease transmitted to humans by animals. The transmission rate, recovery rate, and infected rate of Monkeypox were calculated using the (Runge-Kutta) method in the (MATLAB) program. The cumulative number (total cases) on a daily basis for the period from the beginning of the epidemic to (6/5/2022). The first infection occurred in the United Kingdom, within two weeks, the cumulative number of infections reached (350) infections around the world, the initial values ??were calculated and the parameter value of the average daily transmission of infection was (? = 0.2),Infection rate parameter ( = 0.0625) days and the recovery rate ( then the calculated basic reproduction number is. The estimated parameter of the logisticmodel (?, and was calculated using the (Runge-Kutta) method in the (MATLAB) program.The estimated parameters of (? = 0.16), ( = 0.05), ( and, .The result of the study finds that the spread of a Monkeypox virus is increasing and spreading.